Friedreich’s Ataxia - M.R. Soerjadi; A.H. Sutanto; Bistok Saing; Sahat Halim; Helena Siregar (Indonesian Pediatric Society, 1979)
This is the first report on Friedreich’s Ataxia occurring in an Indonesian family from North Sumatera.